2021
DOI: 10.3892/or.2021.8096
|View full text |Cite
|
Sign up to set email alerts
|

Cell‑cell fusion as an important mechanism of tumor metastasis (Review)

Abstract: Cell-cell fusion is a dynamic biological phenomenon, which plays an important role in various physiological processes, such as tissue regeneration. Similarly, normal cells, particularly bone marrow-derived cells (BMDCs), may attempt to fuse with cancer cells to rescue them. The rescue may fail, but the fused cells end up gaining the motility traits of BMDCs and become metastatic due to the resulting genomic instability. In fact, cell-cell fusion was demonstrated to occur in vivo in cancer and was revealed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…The COVID-19 pandemic drew attention to the connection between pathogens, cancer, and neuropsychiatric disorders, suggesting the possibility of common treatment strategies ( Xu et al., 2020 ). For example, TMEM16F inhibitor niclosamide and its analogs nitazoxanide, hexachlorophene and dichlorophen, present with intriguing anthelmintic, anticancer, and anti-ALS properties, indicating similar pathogenesis ( Peng et al., 2021 ). Indeed, as these agents target S100A4, a protein involved in schizophrenia and inhibited by the phenothiazine class of antipsychotic drugs, a common pathogenetic mechanism is being highlighted ( Malashkevich et al., 2010 ; D’Ambrosi et al., 2021 ).…”
Section: Treatment Strategies For Pathological Cell-cell Fusionmentioning
confidence: 99%
“…The COVID-19 pandemic drew attention to the connection between pathogens, cancer, and neuropsychiatric disorders, suggesting the possibility of common treatment strategies ( Xu et al., 2020 ). For example, TMEM16F inhibitor niclosamide and its analogs nitazoxanide, hexachlorophene and dichlorophen, present with intriguing anthelmintic, anticancer, and anti-ALS properties, indicating similar pathogenesis ( Peng et al., 2021 ). Indeed, as these agents target S100A4, a protein involved in schizophrenia and inhibited by the phenothiazine class of antipsychotic drugs, a common pathogenetic mechanism is being highlighted ( Malashkevich et al., 2010 ; D’Ambrosi et al., 2021 ).…”
Section: Treatment Strategies For Pathological Cell-cell Fusionmentioning
confidence: 99%
“…These macrophage–tumor cell hybrids display increased capacities to evade immunity and migrate [ 7 , 8 , 9 ]. We and others have demonstrated that tumor stem cells and monocytes/macrophages with an M2 phenotype are those more prone to generate tumor hybrid cells (THC) [ 6 , 10 ]. The importance of the cellular interaction between tumor cells and TAMs in BC has been substantiated by the observation of dense tumor cells with strong immunoreactivity with the endocytic receptor for haptoglobin–hemoglobin complexes (CD163, which is characteristic of M2 polarized macrophages) in BC tumor biopsies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cell–cell fusion is a common phenomenon related to physiological processes such as fertilization and tissue repair in which the two lipid bilayer membranes from two cells merge into one. It is known that cancer cells can also fuse with other cells such as leukocytes, fibroblasts, and macrophages (heterotypic cell fusion), as well as with other cancer cells (homotypic fusion) [ 40 , 41 ]. Cell fusion originates bi- or multinucleated cells harboring particular cell attributes of both parent cells.…”
Section: Discussionmentioning
confidence: 99%